2008
DOI: 10.1007/s00792-008-0186-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the two reverse gyrase encoding genes of Sulfolobus solfataricus P2 in relation to the growth phases and temperature conditions

Abstract: Sulfolobus solfataricus, a hyperthermophilic crenarchaeon, contains two genes encoding reverse gyrases, topR1 and topR2. The steady-state level of their transcripts were quantified during the growth phases for cells maintained either at 72, or 80 degrees C, and after temperature changes from one to the other temperature. The transcripts of both genes are weakly expressed, but the highest level is observed in actively dividing cells, and is almost undetectable in cells in decline phase. During the temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Similar to the interplay between gene expression and DNA supercoiling state reported in bacteria (Ahmed et al, ; Menzel & Gellert, , ; Neumann & Quiñones, ; Peter et al, ; Szafran et al, ; Tse‐Dinh, ; Tse‐Dinh & Beran, ), such a level of regulation might also occur for the gene expression of TopR1 in S. solfataricus , as we have previously reported that the topR1 transcript steady‐state level was decreasing with increasing growth temperature and vice versa (Garnier & Nadal, ). In contrast, the topR2 encoding gene was insensitive to the temperature variation applied to promote a change in DNA supercoiling (Garnier & Nadal, ). In the present study, we performed control experiments with cells collected during the exponential phase over a time‐lapse of 6 hr.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to the interplay between gene expression and DNA supercoiling state reported in bacteria (Ahmed et al, ; Menzel & Gellert, , ; Neumann & Quiñones, ; Peter et al, ; Szafran et al, ; Tse‐Dinh, ; Tse‐Dinh & Beran, ), such a level of regulation might also occur for the gene expression of TopR1 in S. solfataricus , as we have previously reported that the topR1 transcript steady‐state level was decreasing with increasing growth temperature and vice versa (Garnier & Nadal, ). In contrast, the topR2 encoding gene was insensitive to the temperature variation applied to promote a change in DNA supercoiling (Garnier & Nadal, ). In the present study, we performed control experiments with cells collected during the exponential phase over a time‐lapse of 6 hr.…”
Section: Discussionsupporting
confidence: 81%
“…Sulfolobus solfataricus P2 cultures were performed as previously described (Garnier & Nadal, 2008). Cells were cultivated either at 80 or 88°C.…”
Section: Culture Of S Solfataricus P2 In Liquid Mediummentioning
confidence: 99%
“…Sulfolobus solfataricus genome encodes two reverse gyrase isoforms, named TopR1 and TopR2, both expressed in vivo (7,31) and showing the same positive supercoiling activity in vitro (MC and AV, unpublished results). Polyclonal antibodies raised against recombinant TopR1 recognized both recombinant proteins and a single band in S. solfataricus cell extracts (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this hypothesis, our previous study evidenced a rapid adjustment of the amount of topR1 mRNA following a temperature shift (up and down), whereas no significant variation of the topR2 mRNA level was observed in response to temperature changes. 26 The presence in a same organism of two closely related topoisomerases is common. For exemple, in E. coli, while the gyrase (type II topoisomerase) negatively surpercoils DNA and removes positive superturns, the topoisomerase IV, the product of ParE-ParC (type II topoisomerase as well), decatenates the chromosome at the end of the replication.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is strongly supported by our previous works, which showed that topR1 and topR2 mRNA are differently regulated in Sulfolobus solfataricus. 26 Hence, in this organism, TopR1 and TopR2 have clearly related amino acid sequences with a relatively low identity (35%) for the whole amino acid sequences. As illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%